Drug-Induced Liver Injury and the Likelihood of Hepatocellular Carcinoma During Chemotherapy for Colorectal Cancer (Meta-Analysis) - T. N. Garmanova; D. R. Markaryan; E. A. Kazachenko; G. V. Tishkin; R. V. Ishchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Tumor diseases are one of the leading causes of death worldwide. Neoadjuvant and adjuvant chemotherapy can potentially lead to drug-induced liver injury and carcinoma. According to the literature review and meta-analysis, the mean weighted incidence of drug-induced liver injuries for all drugs among patients receiving neoadjuvant chemotherapy for colorectal cancer with liver metastases is 63.2 %. The mean weighted incidence of severe liver injury is 37.2 %. However, we have not found clinical reports of liver carcinoma formation due to chemotherapy. At present, we can say that, despite the theoretical possibility, chemotherapy for colorectal cancer is not accompanied by the development of hepatocellular carcinoma.